A Case for Magneto−Inductive Indoor Localization (BEST POSTER AWARD) - Abrudan, T; Markham, A; Trigoni, N (Oxford‚ UK, 2015)
In this work, we show that the magneto-inductive (MI) indoor localization using tri-axial coils possesses unique advantages over the RF-based techniques. The spatial distribution of a generated magnetic field strength can be easily predicted using simple linear models. In addition, the field strength is very stable over time, even in the presence of moving people, which makes MI localization a promising indoor positioning technology.